Muscle force during an acute exacerbation in hospitalised patients with COPD and its relationship with CXCL8 and IGF-I. Issue 9 (28th August 2003) - Spruit, M A; Gosselink, R; Troosters, T; Kasran, A; Gayan-Ramirez, G; Bogaerts, P; Bouillon, R; Decramer, M
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is often associated with peripheral muscle weakness, which is caused by several factors. Acute exacerbations may contribute, but their impact on muscle force remains unclear. Correlations between peripheral muscle force and inflammatory and anabolic markers have never been studied in COPD. The effect of an acute exacerbation on quadriceps peak torque (QPT) was therefore studied in hospitalised patients, and the aforementioned correlations were examined in hospitalised and in stable patients. Methods: Lung function, respiratory and peripheral muscle force, and inflammatory and anabolic markers were assessed in hospitalised patients on days 3 and 8 of the hospital admission and 90 days later. The results on day 3 (n=34) were compared with those in clinically stable outpatients (n=13) and sedentary healthy elderly subjects (n=10). Results: Hospitalised patients had lowest mean (SD) QPT (66 (22)% predicted) and highest median (IQR) levels of systemic interleukin-8 (CXCL8, 6.1 (4.5 to 8.3) pg/ml). Insulin-like growth factor I (IGF-I) tended to be higher in healthy elderly subjects (p=0.09). QPT declined between days 3 and 8 in hospital (mean −5% predicted (95% CI −22 to 8)) and partially recovered 90 days after admission to hospital (mean 6% predicted (95% CI −1 to 23)). QPT was negatively correlated with CXCL8 and positively correlated with IGF-I and lung transfer factor in hospitalised and in stable patients. Conclusions: Peripheral muscle weakness is enhanced during an acute exacerbation of COPD. CXCL8 and IGF-I may be involved in the development of peripheral muscle weakness in hospitalised and in stable patients with COPD.